2023
DOI: 10.1093/narcan/zcad028
|View full text |Cite
|
Sign up to set email alerts
|

The 3D chromatin landscape of rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is a pediatric soft tissue cancer with a lack of precision therapy options for patients. We hypothesized that with a general paucity of known mutations in RMS, chromatin structural driving mechanisms are essential for tumor proliferation. Thus, we carried out high-depth in situ Hi-C in representative cell lines and patient-derived xenografts (PDXs) to define chromatin architecture in each major RMS subtype. We report a comprehensive 3D chromatin structural analysis and characterization o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…2A right and 3 A). 21 The analysis of this site across published chromatin data sets from ENCODE indicated that this is a well-conserved element in all cell types assessed and harbors a potential chromatin subdomain containing the NOTCH1 gene.…”
Section: Resultsmentioning
confidence: 95%
“…2A right and 3 A). 21 The analysis of this site across published chromatin data sets from ENCODE indicated that this is a well-conserved element in all cell types assessed and harbors a potential chromatin subdomain containing the NOTCH1 gene.…”
Section: Resultsmentioning
confidence: 95%
“…It also suggests that analysis of gene regulation and expression in RMS cells considered on the basis of the spatial positioning of the chromosomes they reside on, rather than by clustering genes on the basis of similar function or biological processes, would demonstrate chromosome-specific differences. Others have elucidated characteristics of the organization of the genome in rhabdomyosarcoma cells using techniques including Hi-C, ChiP-Seq, and AQuA-HiChIP (Vicente-Garcia et al, 2017;Gryder et al, 2019;Wang et al, 2023). While these sequencingbased techniques have characterized aspects such as transcription factor binding, interacting genomic regions, histone marks, and regulatory elements such as enhancers, they do not directly assess chromosomal positioning or changes in such positioning, highlighting the need for dedicated analyses of spatial nuclear organization in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…We highlight several of these insights here. Despite “quieter” genomes in sarcoma (lacking high mutation rates), there has been recent compelling evidence that structural variation (SV) is much more common in sarcoma than previously thought, including but not limited to the definitional translocation events ( Chen et al, 2015 ; Gryder et al, 2020a ; Nacev et al, 2022 ; Shukla et al, 2022 ; Xu et al, 2022 ; Choo et al, 2023 ; Wang et al, 2023 ). We anticipate exciting advances in the coming years of deeper characterization of SV in diverse sarcomas, enabled in part by emerging innovative sequencing technologies and platforms.…”
Section: Introductionmentioning
confidence: 99%
“…The depth and power of these clinical genomics studies will enable researchers to uncover key mechanisms of sarcomagenesis in the coming years. Moreover, as we transition from examining linear genomic landscapes into the examination of 3-dimensional (3D) epigenomic landscapes ( Gryder et al, 2020a ; Wang et al, 2023 ; Kim et al, 2024 ), we will begin to integrate genetic and epigenetic mechanisms driving diverse sarcomas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation